2020
DOI: 10.1158/1078-0432.ccr-19-2443
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Durvalumab and Tremelimumab Alone or in Combination in Patients with Advanced Gastric and Gastroesophageal Junction Adenocarcinoma

Abstract: Purpose: This randomized, multicenter, open-label, phase Ib/II study assessed durvalumab and tremelimumab in combination or as monotherapy for chemotherapy-refractory gastric cancer or gastroesophageal junction (GEJ) cancer. Patients and Methods: Second-line patients were randomized 2:2:1 to receive durvalumab plus tremelimumab (arm A), or durvalumab (arm B) or tremelimumab monotherapy (arm C), and third-line patients received durvalumab plus tremelimumab (arm D). A tumor-based IFNg gene signature was prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 28 publications
1
70
1
Order By: Relevance
“…[ 28 32 ] All the selected studies were included in the systematic review, and 3 of 5 were included in the meta-analysis. [ 28 30 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 32 ] All the selected studies were included in the systematic review, and 3 of 5 were included in the meta-analysis. [ 28 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…In the eligible studies, for advanced gastric and gastroesophageal junction adenocarcinoma, the combining durvalumab and tremelimumab displayed a numerically higher ORR than durvalumab monotherapy. [ 30 ] Nevertheless, durvalumab plus tremelimumab showed similar efficacy to durvalumab monotherapy in recurrent or metastatic head and neck squamous cell carcinoma and pancreatic ductal adenocarcinoma. [ 28 , 29 ] It is important to assess what factors might have contributed to the failure of combinatorial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…NCT02340975 is a randomized, multicenter, open-label, phase 1b/2 study, which assessed durvalumab (anti-PD-L1) and tremelimumab (anti-CTLA-4) in combination or as monotherapies for the treatment of chemotherapy-refractory gastric cancer. Response rates were low regardless of monotherapy or combination strategies (27). Although the preliminary observations did not detect an obvious benefit of the combined treatment regimen for patients with advanced gastric cancer, the overall safety profiles still provide support for the study of dual ICI combination therapy.…”
Section: Anti-ctla-4 Antibody and Anti-pd-1/pd-l1 Antibodymentioning
confidence: 83%
“… 2 3 However, data exploring the correlation between RNA signatures and GI cancers, particularly esophageal cancer and colorectal cancers, are still limited. 14 Moreover, a prospective evaluation of the IFN-γ signature was performed in patients with gastric cancer, 15 and the results showed that it failed to guide patient selection, possibly due to the great tumor heterogeneity and complexity of the TME.…”
Section: Discussionmentioning
confidence: 99%